Արդահանի խնդիրը հայ-վրացական հարաբերություններում 1920 թ. աշնանը - Շ. Ա. Թորոսյան (ՀՀ ԳԱԱ հրատ.)
Провинция Ардаган имела жизненно важное значение для Первой Республики Армения, особенно с точки зрения выхода к морю. Ardahan province was of vital importance for the First Republic of Armenia especially in terms of the maritime exit.
Keywords: History; Political Science; Modern History; D History; J Political Science